The role of anticholinergic medication in the prevention of bradycardia during laparoscopic gynaecological surgery. (27th October 2019) - Steer, Anna E.; Ozcan, John; Emeto, Theophilus I.
Abstract : Bradycardia and cardiac arrest are recognised complications of laparoscopic gynaecological surgery. Anticholinergic agents are indicated in the treatment of perioperative bradyarrhythmia; however, their role in the prevention of bradycardia as a result of insufflation of the peritoneum is less well defined. This article systematically reviewed the literature with respect to the role of anticholinergic agents in the prevention of clinically significant bradyarrhythmia during laparoscopic gynaecological surgery. Eight studies were included for review following an extensive database search. This review highlights the paucity of evidence supporting the prophylactic use of anticholinergic agents in preventing clinically significant bradycardia in women undergoing laparoscopic gynaecological surgery.